Measuring relational wellbeing: construct validity in pre-COVID-Era UK; generalizability across COVID-lockdown-Era India, Greece, and UK - Gaines, Stanley O.; Otermans, Pauldy; Spanoudaki, Maria; Aditya, Dev; Chirenda, Netsai (Frontiers in Psychology, 2024)
Aim of the studies: In the present studies, we examine the construct validity and criterion-related validity of a previously unpublished, eight-item measure of relational wellbeing. Method used: First, in two pre-COVID-Era pilot studies within the UK (n’s = 207 and 146, respectively), results of exploratory factor analyses revealed that – with the possible exception of one item regarding close relationships – the items assessed individual differences along a single dimension (i.e., relational wellbeing), rather than two distinct dimensions (i.e., social connections and close relationships). Second, in an initial pre-COVID-Era main study within the UK (n = 192), results of confirmatory factor analyses provided support for the hypothesized one-dimensional factor pattern, although the same problematic item from the pilot studies continued to under-perform relative to the other seven items. Findings: In a subsequent COVID-Lockdown-Era main study across India (n = 205), Greece (n = 354), and the UK (n = 390), results of confirmatory factor analyses established that – after omitting the same problematic item that had surfaced in the preceding studies – a one-dimensional factor pattern provided equally satisfactory fit for the three samples. Original value: Although we had not set out to test a priori hypotheses regarding mean similarities or differences in relational wellbeing among our COVID-Lockdown-Era studies, results of an analysis of variance revealed that persons within the UK scored significantly lower in relational wellbeing than did persons in India or the UK. Limitations: As noted above, one particular item repeatedly performed poorly in factor analyses; this item ideally should be dropped from the relational wellbeing scale in future research.